1981
DOI: 10.1111/j.1476-5381.1981.tb10446.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Atropine and Oxotremorine on Acetylcholine Release in Rat Phrenic Nerve‐diaphragm Preparations

Abstract: Atropine (10−5m) enhanced the release of [3H]‐acetylcholine from rat isolated hemidiaphragms, previously incubated with [3H‐methyl]‐choline, stimulated via their phrenic nerves. Oxotremorine (10−5m) did not affect the stimulated release of [3H]‐acetylcholine but antagonized the facilitatory effects of atropine (10−5m). It is suggested that there are presynaptic inhibitory muscarinic receptors that modulate the release of acetylcholine in the phrenic nerves of the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…In some experiments, muscarinic agonists have inhibited ACh release from motor nerve terminals, whereas in others, ACh release was increased (Abbs and Joseph, 1981;Wessler et al, 1987;Arenson, 1991;Robitaille et al, 1997;Santafé et al, 2007). At the vertebrate NMJ, the activation of m2 AChR reduced the release, whereas the activation of m1/m3 AChR facilitated the release (Slutsky et al, 2001;Minic et al, 2002;Oliveira et al, 2002Oliveira et al, , 2009Dudel, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments, muscarinic agonists have inhibited ACh release from motor nerve terminals, whereas in others, ACh release was increased (Abbs and Joseph, 1981;Wessler et al, 1987;Arenson, 1991;Robitaille et al, 1997;Santafé et al, 2007). At the vertebrate NMJ, the activation of m2 AChR reduced the release, whereas the activation of m1/m3 AChR facilitated the release (Slutsky et al, 2001;Minic et al, 2002;Oliveira et al, 2002Oliveira et al, , 2009Dudel, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the myenteric plexus in guineapig ileum had a muscarinic receptor which modulated ACh release by a negative feed-back mechanism (Kilbinger & Wagner, 1975;Sawynok & Jhamandas, 1977; Kilbinger, 1977;Fosbraey & Johnson, 1978; Kilbinger & Wagner, 1979;Gustafsson, Hasqvist & Lundgren 1980;Kilbinger & Wessler, 1980a,b;Fosbraey & Johnson, 1980;Kilbinger & Kruel, 1981). Furthermore, it has been suggested that similar presynaptic muscarinic receptors exist in cerebral cortex of the cat (Dudar & Szerb, 1969), in central cholinergic nerves of rat (Polak, 1967;Szerb & Somogyi, 1973;Kato, Collier, Ilson & Wright, 1975;Szerb, Hadhazy & Dudar, 1977;Szerb, 1977;Nordstrom & Bartfai, 1980), in the electric organ of Torpedo (Michaelson, Avissar, Kloog & Sokolovsky, 1979;Dunant & Walker, 1981) and in rat phrenic nerve-diaphragm prepara-0007-1188/82/090075-08 $01.00 tions (Abbs & Joseph, 1981). On the other hand, Kato et al (1975) found that the cat superior cervical ganglion did not have such a presynaptic muscarinic receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The type of cholinoceptor sites involved in the feedback regulation however, is controversial. Muscarinic inhibitory (Duncan & Publicover, 1979;Michaelson et al, 1979;Abbs & Joseph, 1981;Somogyi et al, 1987) and excitatory (Das et al, 1978;Wali et al, 1987;Wessler et al, 1987) prejunctional cholinoceptors have been reported at vertebrate neuromuscular junctions and in the Torpedo electric organ. In the presence of tubocurarine, a frequency-dependent decrease of evoked ACh release was obtained which suggested the presence of nicotinic prejunctional cholinoceptors mediating a positive feedback control of evoked transmitter release (Glavinovic, 1979a;Magleby et al, 1981;Wessler et al, 1986;Matzner et al, 1988).…”
Section: Introductionmentioning
confidence: 99%